2020
DOI: 10.1590/0001-3765202020191533
|View full text |Cite
|
Sign up to set email alerts
|

Seseli petraeum M. Bieb. (Apiaceae) Significantly Inhibited Cellular Growth of A549 Lung Cancer Cells through G0/G1 Cell Cycle Arrest

Abstract: Seseli L. is an important genus of the Apiaceae family, with a large number of aromatic species. It is used in traditional medicine extensively, but there is quite limited information on their phytochemicals and biological activities. Seseli petraeum M. Bieb. grows in Northern Anatolia, and there are no phytochemical studies on this species. In the present study, we aimed to investigate the effect of the extracts of S. petraeum on A549 lung cancer cell proliferation. For this purpose, the antiproliferative eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Seseli L., belonging to the Apiaceae family, is a genus distributed in Europe, Africa, Asia, North America, and Australia [27] that counts thirty-four species for Europe in the Flora Europea [28]. This genus consists of aromatic herbs and economically important species used as food, spices, condiments, and ornamentals [29].…”
Section: Introductionmentioning
confidence: 99%
“…Seseli L., belonging to the Apiaceae family, is a genus distributed in Europe, Africa, Asia, North America, and Australia [27] that counts thirty-four species for Europe in the Flora Europea [28]. This genus consists of aromatic herbs and economically important species used as food, spices, condiments, and ornamentals [29].…”
Section: Introductionmentioning
confidence: 99%
“…The hexane extract of the root exhibited potent inhibition on A549 cancer cell growth at the 24th h (IC 50 : 3.432 mg/mL). The results also showed that the hexane extract displayed the cytotoxic effect through an arrest at the G0/G1 phase of the cell cycle and induced apoptosis as well as DNA damage in A549 cells [8]. Besides, a recent study showed that chlorogenic acid, a main compound identified in the Seseli species in the current study, did not reduce viability of human promyelocytic leukemia cells (HL-60) and human acute T-cell leukemia cells (Jurkat).…”
Section: Resultsmentioning
confidence: 41%
“…In light of the ethnobotanical uses; several studies have been conducted on the biological activities of the members of this genus. Previously, antibacterial, anticancer, anti-inflammatory and antinociceptive effects have been confirmed for several Seseli species [2,[6][7][8]. Furthermore, a number of scientific reports have demonstrated Seseli species to contain volatile oils with important pharmacological potentials.…”
Section: Introductionmentioning
confidence: 95%
“…Since Apiaceae are a very important source of phytochemicals, bioactive compounds with nutritional potential, polyphenolic compounds, polyethylenes, and terpenoids, they are used for cancer prevention and treatment (31)(32)(33). Also, the anticancer properties of several plants from this family, such as Ferulago Mughlea Pes ¸men, Seseli petraeum, and Petroselinum crispum, have been investigated in other research studies (33)(34)(35). This is the first study of the anticancer and apoptosis-inducing properties of F. subpinnata on cancer.…”
Section: Discussionmentioning
confidence: 99%